An efficient long-wavelength single-frequency DBR Tm3+-doped fiber laser at 2.1 μm based on 1610 nm in-band pumping - Kaixuan Wu; Changsheng Yang; Guowu Tang; Weichao Wang; Hengxiao Huang; Xin Zhang; Chun Zeng; Pengxing Huang; Qilai Zhao; Shanhui Xu; Zhongmin Yang (Applied Physics Express)
Based on a 2.0 cm long Tm ^3+ -doped fiber (TDF) and in-band pumped configuration, an efficient long-wavelength single-frequency distributed Bragg reflector (DBR) fiber laser at 2097 nm is demonstrated experimentally. With delicate optimization of the TDF length and the pump wavelength to consider the effective cavity length and pump absorption, a stable single-longitudinal-mode laser output of 10.4 mW is achieved under 1610 nm in-band pumping. The measured optical signal-to-noise ratio of the fiber laser is more than 59 dB, the linewidth is less than 9.1 kHz, and the relative intensity-noise is below −130 dB Hz ^−1 for the frequencies above 4 MHz. To the best of our knowledge, this is the first demonstration of a single-frequency DBR Tm ^3+ -doped fiber laser at a long operation wavelength of 2.1 μm.